Pedagogia dos multiletramentos: consciência crítica, agência e empoderamento no Ensino Fundamental - Silva, Cleiton Reisdorfer (2023)
Language teaching in a school context is an activity rich in pedagogical possibilities, and it is up to the teacher to seek and select teaching approaches that can be meaningful for the context and for the students' demands. In this sense, considering the concepts of pedagogy (DURKHEIM, 2011; LIBÂNEO, 2002; SAVIANI, 2013), literacy projects and multiliteracy pedagogy (KLEIMAN, 2000; ROJO; ALMEIDA, 2012; KALANTZIS et al., 2016) and Critical Analysis of Genres (ACG) (MOTTA-ROTH, 2008a; 2008b) and the theories that support it – Critical Discourse Analysis, Socio rhetoric and Systemic-Functional Linguistics, the general objective of this thesis is to investigate to what extent a multiliteracies project enables, the elementary school students, to became agents of the learning process, their social participation and critical reflexivity. The investigation, of an ethnographic nature (ERICKSON, 1990), was carried out with ten students in the ninth year of elementary school at a school in the countryside of the state of Rio Grande do Sul, over the years 2020 and 2021. Seeking to fulfill the specific objectives, we divided the research into three stages: context mapping, didactic activities and project evaluation. First, questionnaires and interviews were carried out to describe and analyze the students' situated practice, mapping the context of literacy practices and events in which they participate. In a second moment, considering the mapping data and the knowledge processes of pedagogy, we elaborated, developed and analyzed didactic-pedagogical activities in a multiliteracy project based on a problem of interest of the students. Finally, we critically evaluated the multiliteracies project based on reflective reports produced by students throughout the project's didactic activities. Having carried out the analysis of the data generated throughout the research, we argue that a multiliteracy project adapted to a Brazilian teaching context promotes agency and critical reflexivity in elementary school students. To make this possible, we listed the following elements as principles of this project: i) mapping the context of students' literacy practices and events to understand how school learning interacts with knowledge built outside of school; ii) social engagement and search for resolution of social problems; iii) teaching based in the context and problem determined by the students, focusing on knowledge processes and multimodal genres; iv) curricular flexibility for the implementation of the didacticpedagogical proposal, resources for the school to facilitate the implementation of the social practices idealized by the students and domain theoretical-practical by the teacher; v) collaborative approach between students and teacher at all stages, so that the mapping can be done efficiently, the didactic activities are productive, empowering the students to act socially, and the evaluation takes place in a transparent way.